Calcitriol infra venous therapy in routinely hemodialyzed patients with secondary hyperparatyroidism - Mochammad Sja'bani Mochammad Sja'bani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Secondary hyperparathyroidism is common in patients with chronic renal failure. Secondary hyperparathyroidism with vitamin D deficiency may increase renal osteodystrophy.Objective: To determine the blood intact parathormone (iPTH) level in routinely hemodialyzed patients with secondary hyperparathyroidism undertaking calcitriol intravenous therapy once in two weeks. Methods: a double blind randomized clinical trial had been done in 32 chronic renal failure patients from 41 secondary hyperparathyroidism who underwent regular hemodialysis in Dr. Sardjito Hospital Yogyakarta. All patients received intravenous calcitriol 11.1.g or placebo twice a week after dialysis for 2 weeks. The proportion of the decrease of iPTH level at least 30%; calcium, and phosphate levels in calcitriol (16 patients) and in placebo (16 patients) group were measured.Results: The decrease of iPTH at least 30% in calcitriol group were 12 patients (75%) and in placebo group 6 patients (37.5%) (p> 0.05). In calcitriol group there were 4 patients (25%) with hypercalcemia and 6 patients (37.5%) with hyperphosphatemia, whereas in placebo group 5 patients (31.3%) with hypercalcemia and 5 patients (31.3%) with hyperphosphatemia (p>0.05).Conclusion: Calcitriol intravenous therapy for 2 weeks might decrease iPTH at least 30%.Key words: secondary hyperparathyroidism - chronic renal failure - osteodystrophy - intact parathormone -calcitriol